The translation style in the novel Mirname by Jan Dost - Amin, آ.د. سیروان جـەبار ئەمین; محمود, م.م. مهدی أحمد محمود (Sulaimani Journal for Humanities, 2025)
Narration as a process of presenting and expressing creates an important part of human’s life, therefore humans in the beginning of life uses narration to talk about the events that happened in the past. This thesis “Narrative Skills in Jean Dost’s Novel Mirmama” is an opportunity to introduce Mirnama Novel and its techniques of narration. It is divided into two parts: in the first part, we discussed the terms and methods of narration and narrator and their types. In the second part, we described the places and the characters; we also discussed dialogues and monologues that are directly and indirectly presented in Mirnama. We also wrote about the content, properties, and the difference of narration. Finally, the result, table of references, and the summary of the research are presented in English language.
Keywords: Time; Place; Character; Dialogue and Monologue